Extended Draf IIb Procedures in the Treatment of Frontal Sinus Pathology - Tomasz Gotlib; Marta Held-Ziółkowska; Kazimierz Niemczyk (Clinical and Experimental Otorhinolaryngology, 2015)
ObjectivesDraf IIb approach provides wide, unilateral access to the frontal sinus. This approach can be extended without destruction of the contralateral frontal sinus drainage pathway, performed during Draf III (modified Lothrop) procedure. There is limited data in the literature regarding the use of modified Draf IIb procedures.MethodsPatients treated with extended Draf IIb procedures in a single center were retrospectively assessed.ResultsTen patients were identified, including 2 cases of osteoma, 1 inverted papilloma, 1 carcinoma, 5 mucoceles, and 1 chronic rhinosinusitis patient. Six patients had undergone prior surgery, including external procedures in 3 cases. Modifications of Draf IIb were classified as the following: removal of the anterosuperior nasal septum adjacent to the nasal beak, removal of the intersinus septum, and a combination of the above-mentioned methods (upper nasal septum and intersinus septum removal). There were 3 patients operated on with type 1 modification, one patient with type 2 modification, and 6 patients with type 3 modification. There were no perioperative complications.ConclusionIn selected cases, extended Draf IIb procedures are safe and effective in the treatment of frontal sinus disease.